Waqf Transformation in Morocco: From Traditional Charity to Modern Socio-Economic Instruments - Fouad Larhzizer; Imam Buchari; Sari Utami (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2026)
Islamic philanthropic instruments such as waqf face a profound paradox within the global capitalist system. While embodying ideals of substantive economic justice and community empowerment, in practice they often become subsumed by the dominant economic logic, limiting their transformative potential. This study aims to analyze the transformation of Islamic philanthropy models in Morocco, particularly the shift from traditional waqf to modern socio-economic instruments. Employing a qualitative library research approach with historical-institutionalist and case study perspectives, this research synthesizes academic literature, legal documents, and institutional reports to examine the characteristics of traditional waqf, the drivers of its transformation, and its implications for socio-economic development. The findings reveal that waqf transformation in Morocco is driven by the interplay of state intervention, economic modernization, and global philanthropic models, resulting in a transition toward productive and institutionalized waqf. However, this process is non-linear and marked by tensions between religious values, market logic, and governance structures. The study argues that waqf reform is not merely technical but constitutes a broader socio-institutional transformation requiring the integration of innovation with Sharia principles to ensure Islamic philanthropy remains both effective and ethically grounded in advancing sustainable socio-economic development in Morocco and comparable contexts